'Speaking French alive': learner perspectives on their motivation in Content and Language Integrated Learning in England. Issue 1 (2nd January 2019) - Bower, Kim
ABSTRACT: This article reports part of an empirical research study undertaken in state secondary schools in England in 2012/2013, to investigate the extent to which Content and Integrated Learning (CLIL) promotes pupil motivation in the teaching of modern foreign languages (MFLs). Pupil perspectives of the impact of CLIL on their motivation are presented from two schools where different models of CLIL are practised. Firstly, a Partial Immersion Model of more than two subjects, for one Year 8 (Y8) mixed ability group, was taught for over six hours a week by a language teacher. Secondly, a curriculum Subject Strand Model was taught for one lesson per week by a geography specialist in Year 7 (Y7) and Y8 ability sets. Data are presented from student questionnaires and focus groups. This article offers a unique contribution to the field by its focus on pupil motivation linked to contrasting CLIL contexts in England. The findings reveal positive perceptions of CLIL methodology and high levels of concentration, effort, enjoyment and progress, especially in the Partial Immersion Model, where the depth of relationship and cooperation and the enhanced levels of linguistic competence both lead to greater pupil engagement and motivation.